Effectiveness of Collaboration between Local Government and The Regional People’s Representative Council (DPRD) in the Formulation of Regional Regulations in Cirebon City - Karso, Karso; Setiadi, Ade; Amiarsa, Pandji (Universitas Negeri Semarang, 2025)
This study examines the effectiveness of collaboration between the Local Government and the Regional People’s Representative Council (DPRD) in the formulation of regional regulations (Peraturan Daerah or Perda) in Cirebon City. The formulation of regional regulations is an essential element of local governance and reflects the quality of policy coordination, democratic participation, and institutional capacity at the regional level. However, in practice, collaboration between the executive and legislative bodies often faces obstacles such as overlapping interests, limited synchronization of programs, and differing policy priorities. The purpose of this research is to analyze the level of effectiveness of collaboration between the Cirebon City Government and the DPRD in the process of drafting and determining regional regulations, and to identify supporting and inhibiting factors in the collaboration process. The study applies a qualitative-descriptive approach supported by primary data collected through in-depth interviews, document analysis, and observation. The theoretical foundation of this study is based on the concept of collaborative governance (Ansell & Gash, 2007), which emphasizes participation, consensus, and joint decision-making as the main pillars of inter-institutional cooperation. The findings indicate that the collaboration between the Local Government and DPRD in Cirebon City has been moderately effective. The two institutions have established routine communication, mutual consultation, and coordination forums. However, collaboration has not yet reached an optimal level due to differences in political orientation, limited bureaucratic capacity, and inadequate public involvement in the early stages of policy formulation. The study recommends strengthening the collaboration framework through improved communication mechanisms, transparent consultation procedures, and capacity-building programs for legislative and executive members. This research contributes to the understanding of collaborative governance within Indonesia’s decentralized administrative system. It highlights that effective collaboration between political and bureaucratic actors is not only a procedural requirement but also a fundamental condition for the success of democratic governance at the regional level.